Experimental analysis of aerosol dispersion and containment solutions in aircraft cabins - Mahmoud, Seif (Kansas State University, 2021)
This dissertation is focused on the dispersion and containment solutions of possibly infectious aerosols in aircraft cabins. In this study, a Boeing 767 mockup cabin, a Boeing 737 section, and a modified cabin were utilized. The Boeing 767 and the modified cabins have eleven rows with each row consisting of seven seats in a 3-2-3 configuration. The Boeing 737 section has five rows of seats with six seats in each row in a 3-3 configuration. Seats were occupied by inflatable manikins that generate approximately 100 W of sensible heat per manikin, representing heat load from a sedentary human being and cabin equipment. An aerosols containment solution called “ISOPass” was tested in the different aircraft cabins. A total of 183 tests were performed using; two tracer gas source types, different source seat locations, different ISOPass conditions in the three different aircraft cabins. The source types were a continuous injection source and a coughing manikin. The source locations were two seats at each cabin side, a front seat, a middle seat, and a rear seat. The ISOPass conditions were ISOPass deployed and ISOPass undeployed. Four injection source locations were selected. A 25.4 mm (1 inch) inner diameter copper tube was used as the continuous injection source. A mix of 5 L/min (0.176 ft³/min) of carbon dioxide and 3.07 L/min (0.108 ft³/min) of helium was injected at the average of seated passenger breathing level of 1.25 m (4.1 ft) above the cabin floor. A total of 42 tests were conducted in matching pairs. It was noticed that the contaminant transport pattern is dominated by the cabin airflow pattern in the near field and by distance in the far field. Also, the contaminant concentration was not necessarily the same at similar radial distances in different directions from the source, especially in the near field. Furthermore, tracer gas concentrations at some seats were higher than the source seat due to the airflow pattern inside the cabin. Using a coughing manikin of a 4.2 L (0.148 ft³) cough volume, 93 tests were conducted in matching triplets. Five coughing manikin locations were selected in different locations inside the cabin. Tracer gas samples were collected up to 3.35 m (11 ft) from the manikin in different orientations. Without the ISOPass and due to the cough momentum, the tracer gas concentration at further distances from the coughing manikin were sometimes higher than in the vicinity of the manikin. Also, tracer gas concentration at the rear of the cabin was negligibly affected by the coughing manikin compared to the longitudinal or diagonal directions. The ISOPass, when deployed in different aircraft cabins and using either source types, was proven an effective tool to contain aerosols from spreading to other passengers and crew. Smoke visualization was performed at five different locations to qualitatively analyze the dispersion of the tracer gas in the aircraft cabin. The smoke visualization results provided an explanation for some of the phenomena that were recorded using the tracer gas measurements such as the increase in the tracer gas concentration in some seats over the source seat.
Keywords: Aircraft; Infection; Contaminant; Airflow; Dispersion; Aerosol